An exploratory study of universities students’ regulation of cognition and entrepreneurial intention. - Lope Pihie, Zaidatol Akmaliah; Bagheri, Afsaneh; Abdullah Sani, Z. Husna (2013)
Entrepreneurship research has mostly examined the association between cognitive styles and individuals’ entrepreneurial intentions. However, regulation of cognition as the capacity to plan, monitor and evaluate learning highly affects one’s selection into entrepreneurship. This study aimed to explore university students’ regulation of cognition and their entrepreneurial intentions. The sample consisted of 722 students from three public and two private Malaysian universities. The findings showed students are different regarding their awareness of their regulation of cognition. While public university students scored higher in four aspects of regulation of cognition including planning, information management strategies, comprehension monitoring, and evaluation, students from private universities scored higher in debugging strategies and intentions to become an entrepreneur than their counterparts. Implications of the findings for entrepreneurship research and education and agendas for future research are discussed.